ASSESSMENT OF THE WEIGHT OF FACTORS INFLUENCING FOOD LOSSES USING FUZZY MULTI-CRITERIA ANALYSIS - Nedeljković, Miroslav; Papović, Zoran; Krstić, Svetozar (Economics of Agriculture, 2024)
The purpose of the paper is to show, through the selection of given criteria, which of them has the greatest impact on food losses in an agricultural-food company. For this purpose, an innovative expert method of multi-criteria decision-making, SiWeC (Simple Weight Calculation), and its fuzzy variant, was applied. The results show that the criteria “poor handling of products during transport” and “inadequate packaging and handling of products” have the greatest impact. Considering the already existing plan of the company to train this part of the work processes, the expert assessment confirms the results of the research. Also, the successful use of this method with the application of fuzzy logic was confirmed, and future research should be directed towards the development of new ways of researching the influence of individual factors on the entire process of supplying food to end consumers.